2018
DOI: 10.1002/hyp.11500
|View full text |Cite
|
Sign up to set email alerts
|

Time–space fractional governing equations of transient groundwater flow in confined aquifers: Numerical investigation

Abstract: In order to model non‐Fickian transport behaviour in groundwater aquifers, various forms of the time–space fractional advection–dispersion equation have been developed and used by several researchers in the last decade. The solute transport in groundwater aquifers in fractional time–space takes place by means of an underlying groundwater flow field. However, the governing equations for such groundwater flow in fractional time–space are yet to be developed in a comprehensive framework. In this study, a finite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…On the other hand, those of Well 2 represented mainly Gaussian characteristics, which sometimes failed to capture the peaks of the skewedprobability distributions of Well 2 groundwater levels. Time series analysis of groundwater level fluctuations of the two wells demonstrated that the observed fractal behavior is site specific, and there is a need for generalized governing equations of groundwater flow processes that can model both the long-memory behavior and the Brownian finite-memory behavior Tu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, those of Well 2 represented mainly Gaussian characteristics, which sometimes failed to capture the peaks of the skewedprobability distributions of Well 2 groundwater levels. Time series analysis of groundwater level fluctuations of the two wells demonstrated that the observed fractal behavior is site specific, and there is a need for generalized governing equations of groundwater flow processes that can model both the long-memory behavior and the Brownian finite-memory behavior Tu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noticed that the applications of FADEs in hydrology are mainly focused on the simulation of tracer experiments. Previous studies have shown that FADEs can also be used to simulate the change of subsurface water tables (Tu, Ercan, & Levent, 2018) and the transport of suspended sediment in an unsteady flow (Nie et al, 2018), to describe the vertical distribution of suspended sediment in a steady flow (Nie et al, 2017), and to forecast pollutant drift on coastal water surfaces (Qin et al, 2017). Yu et al (2018) also proved that the fractional derivate model could be used to simulate colloid transport in the dense vegetation and soil systems.…”
Section: Challenges and Suggestions For Future Workmentioning
confidence: 99%
“…The elementary structure of time-fractional convection-dispersion equation (TFCDE) uses the derivative term with fractional index instead of derivative term with integer order in time where the range of fractional order derivative is generally considered to be 0 to 1 but it can also be further extended to the range 1-2 [17][18][19][20]. The advantage of using fractional convectiondispersion equation (FCDE) over classical form of CDE is that fractional one is much more applicable to simulate the variation of the subsurface water table and also for the simulation of colloid migration in the soil system and dense vegetation [21,22]. Due to nonlinearity arises from the fractional order terms, it is quite complicated to present analytical or numerical solutions for FCDE as compare to classical one.…”
Section: Introductionmentioning
confidence: 99%